Salafisasi Tradisi Intelektual Islam: Al-Albānī dan Suntingan Riyāḍ Al-Ṣāliḥīn - Sunarwoto Sunarwoto (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
Salafis are known for their strong commitment to practicing Islam as literally as possible in accordance with the understanding of the Salaf (pious forefathers) generation in their daily life. Despite their claim to the purity of their Islamic interpretation, Salafism is historically constructed. This article deals with the taḥqīq (editing) of Riyāḍ al-Ṣāliḥīn endeavored by a renowned Salafi scholar, Nāṣir al-Dīn Al-Albānī. It aims to demonstrate how Salafism has been constructed. In doing so, it tries to detail how Salafism has become increasingly mainstreamed, a process we might call “Salafization”. This article argues that Al-Albānī did “Salafization” of Islamic intellectual tradition through taḥqīq. Using Gérard Genette’s paratextual analysis, this article unveils practices and discourses surrounding Al-Albānī’s textual editing. These practices and discourses were guided by his Salafi ideology. In his edition of Riyāḍ al-Ṣāliḥīn, there are three examples where Al-Albānī corrected popular Islamic understanding, including the relationship between intention (nīyah) and action (ʿamal), asmāʾ wa ṣifāt, and traditional religious practices and rituals.